Pengaruh Faktor Ekternal Perusahaan Terhadap Harga Saham Di Indonesia - Nova Nova (Fakultas Ekonomi Universitas Almuslim Bireuen, 2021)
The aim of this research is to examine the influence of company external factors such as level inflation and interest rates on stock prices in Indonesia. The data used is data monthly from January 2017 – December 2019. Data analysis techniques used in This research is multiple linear regression. The research results show that inflation and ethnicity interest partially influences stock prices in Indonesia.